CHALLENGES EXPERIENCED BY HISTORY LEARNERS DURING ASSESSMENT USING THE MEDIUM OF ENGLISH - Rapetsoa, JM; Singh, RJ (South African Journal of Higher Education, 2016)
This study investigated the challenges that history learners in rural black schools are faced with during assessments when using English as the language of learning and teaching. The aim of the study was to investigate whether English, which is used as a language of learning and teaching in schools, is a barrier to the learning and teaching of history. It is argued that the use of English has implications on the results that learners obtain during summative assessment. The literature reviewed revealed that any language of learning and teaching, which is not the mother tongue of learners, has an impact on the process of learning. Assessment, which determines whether the learning outcomes have been attained or not, is affected by factors like the type of assessment, for example, formative or summative; the purpose of assessment and the rules and regulations that goes along with assessment. In order to gain a greater insight and a comprehensive understanding of the research problem, a qualitative approach was used with some quantitative elements. A multiple-case study design was adopted. The research instruments employed were interviews, document analysis and observations. The findings indicated that the environment in which the learners learnt a second language had an impact on the learners’ language proficiency. Furthermore, it was found that assessment poses a challenge to learners, in addition to the challenges caused by the language. The findings also indicated that educators and the learners preferred to use English as a language of learning and teaching and not their mother tongue. This was despite all the challenges they faced when they used English. An important recommendation was to develop mother-tongue terminology in history.